The Republic of Indonesia's Free and Active Political Policy in International Relations Between Nations - Haryanto, Haryanto (Semarang State University Undergraduate Law and Society Review, 2023)
A country's foreign policy is a means to achieve the desired goals for the national interests of the country. Likewise with Indonesia, establishing cooperation in the international world and between countries is not a taboo. With the principle of free and active politics as a guideline for Indonesia in exploring the wilderness of the international world which is full of various interests and conflicts, Indonesia must be able to formulate its foreign policy policies well, not only limited to national interests but must be able to show contributions to the international world so that Indonesia's name can be taken into account in its goal of becoming a Middle Power country. Indonesia's foreign policy line cannot be separated from the views and ideology of the ruling regime, whether using persuasive or confrontational diplomacy. Even the principle of free and active which is currently held has an ambiguous interpretation or meaning, whether the free and active in question is free in the sense of being neutral in international conflicts between nations, but still actively providing solutions and contributions in resolving conflicts, or free and active in the context of being free to have one's own views and stances to support or not support an entity or country in an international conflict based on the foundation and limitations of the country's constitution. Interestingly, both of these meanings of active freedom have been applied in Indonesia's foreign policy.